A novel generation method of oscillatory rotating eddy current for crack orientation determination and detection in metal plates. (July 2018) - Xiucheng, Liu; Jieming, Yang; Bin, Wu; Cunfu, He
Abstract: A novel generation method of oscillatory rotating eddy current (OREC) is proposed to solve the problems in the conventional rotating eddy current (REC) method. Although the REC method can provide the uniform sensitivity to all the cracks with different distribution angles in non-ferromagnetic materials, eddy current signal patterns can be applied only in the rough quantification of crack orientation. In ferromagnetic materials, due to the cancellation effect between the magnetic flux leakage and eddy current mechanisms, when the angle between the crack direction and the excitation current direction was about 45°, it was difficult to detect the crack with the conventional REC method. Therefore, amplitude-modulated excitation currents were introduced into the REC test and then oscillatory rotating eddy current are induced to interact with the cracks in the study. The frequency of the modulation signal determined the spatial rotation speed of the OREC field. Then, the compound profiles of the detected carrier signals were extracted and redrawn in the polar diagram to demonstrate 8-shaped or 4-Pl signal patterns. Finally, the angle between straight lines connecting the maximum signal positions of 8-shaped or 4-Pl trajectories was estimated as the feature parameter for determining crack orientation. The feature parameter was used to characterize all the cracks with different distribution angles in both non-ferromagnetic and ferromagnetic materials. The proposed OREC method realized an angular resolution of 15° in crack orientation determination. Highlights: The conventional REC technique can only roughly quantify the crack orientation. Cracks with some orientations are difficult to detect using the conventional REC. Oscillatory REC method is proposed to resolve the problems of conventional REC. Oscillatory REC provides high accuracy in crack orientation determination.